Studi Desktiptif Tentang Motivasi Orang Tua Memilih Sekolah Katolik untuk Membentuk Sikap Pluralisme Siswa - Eric Wirawan, Cosmas; Antony, Rian (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
This study aims to understand parents' motivations in choosing Catholic schools as a means of fostering inclusive attitudes towards social differences in children, particularly in the context of Indonesia's multicultural society. This study used a qualitative approach with a narrative design. Meanwhile, purposeful sampling was used to select five parents of students involved in the study. In-depth interviews were conducted with parents of students at SMK Pius X Magelang, Central Java. The results of the study show that parents' motivation in choosing Catholic schools is not only because of their academic reputation, but also because of the values of discipline, morality, openness, and love that are instilled. However, there are challenges faced, such as relatively high education costs, issues of exclusivity, and concerns about Christianisation. However, Catholic schools are still considered capable of having a positive impact on children, especially in shaping integrity, creativity, and tolerance. These findings are in line with Durkheim's social structure theory, which emphasises the function of education in maintaining social order, as well as Freire's critical pedagogy theory, which emphasises dialogue, critical awareness, and liberation. Previous studies also reinforce that Catholic schools play an important role in instilling the values of pluralism and character education in a diverse society. Thus, Catholic schools have great potential as strategic partners for parents in building a generation that is superior, has integrity, and is inclusive.